Endoscopic Endoluminal Radiofrequency Ablation and Single-Operator Peroral Cholangioscopy System (SpyGlass) in the Diagnosis and Treatment of Intraductal Papillary Neoplasm of the Bile Duct: A Case Report and Literature Review - Tang, Wei; Qiu, Jian-Guo; Wei, Xu-Fu; Xiao, Heng; Deng, Xin; Wang, Shao-Dong; Du, Cheng-You; Wu, Qiao (Frontiers in Medicine, 2021)
Background: Intraductal papillary neoplasm of the bile duct (IPNB) is a rare biliary benign tumor with atypical clinical features, and is frequently misdiagnosed. Its treatment is limited and surgical resection is thought to be the only therapeutic option for IPNB patients. With the aim of increasing the early diagnosis rate of IPNB and providing more therapeutic options for surgeons, we innovatively put forward the concept of combined utilization of SpyGlass and endoscopic endoluminal radiofrequency ablation (ERFA) in the diagnosis and treatment of IPNB. Case Presentation: A 85-year-old woman was referred to our hospital due to right upper quadrant abdominal pain. The image examinations indicated suspicious filling defects at the upper common bile duct. Further evaluation of SpyGlass cholangioscopy showed multiple reddish villous lesions at the left hepatic duct and SpyBite biopsy under direct visualization demonstrated papillary low-grade dysplasia. In consideration of the advanced age and preference of the patient, the novel ERFA therapy was performed. The procedure was successful without periprocedural complications, the patient recovered uneventfully and was discharged 2 days after the operation. Upon follow-up, the patient was asymptomatic and in good physical condition at 8 months postoperatively. Conclusion: Preliminarily, we demonstrate that the strategy of combination of SpyGlass and ERAF seems to be a promising, feasible, well-tolerated, and safe management for IPNB patients. However, more data with larger patient volume are needed to evaluate its outcomes further.